Comparação entre técnicas coproparasitológicas no diagnóstico de ovos de helmintos e oocistos de protozoários em cães. - Táparo, Cilene V.; Perri, Sílvia H. V.; Serrano, Anna Cláudia M.; Ishizaki, Miriam N.; Costa, Taiana P. da; Amarante, Alessandro F. T. do; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2006)
In this study we evaluated the frequency of enteroparasites in pet dogs and their association with age, sex and breed, as well as the efficiency of the Willis-Mollay, Faust, Sedimentation and Direct exam methods. By these methods we processed 401 fecal samples. The samples were positive in the following percentages: Ancylostoma spp. (53.1%), Toxocara canis (20.7%), Cystoisospora ohioensis (15.7%), Trichuris vulpis (3.7%), Dipylidium caninum (2.5%) and Taenia spp. (1.0%). Toxocara canis (67.3%) and C. ohioensis (47.3%) showed higher positivity in the puppies. The Willis-Mollay technique was more efficient in the diagnosis of Ancylostoma spp. and T. canis eggs. The Direct method was the least efficient. It was found that the majority of the cases of D. caninum were diagnosed by the Sedimentation method (8=2.0%), while for T. vulpis Willis-Mollay (12=3.0%) and Sedimentation (13=3.2%) were more efficient. In view of these results, we can recommend the association of Willis-Mollay and Sedimentation methods for the diagnosis of gastrointestinal helminths. Due to the elevated occurrence of Ancylostoma spp. and T. canis, which are involved in zoonotic diseases, it becomes necessary to apply more efficient prophylaxis of canine intestinal parasitosis at the City of Araçatuba, state of São Paulo.
Comparison between coproparasitological techniques for the diagnosis of helminth eggs or protozoa oocysts in dogs
Keywords: animal; animal parasitosis; comparative study; dog; feces; female; helminth; male; methodology; oocyst; parasite identification; parasitology; protozoon; Animals; Dogs; Feces; Female; Helminthiasis, Animal; Helminths; Male; Oocysts; Parasite Egg Count; Parasitology; Protozoa; Protozoan Infections, Animal